Developmental-form-specific DNA-binding proteins in Chlamydia spp. - Wagar, E A (1988)
We identified DNA-binding proteins specific to the elementary body (EB) developmental form of Chlamydia spp. Chlamydial proteins from whole lysates were separated by polyacrylamide gel electrophoresis, transferred to nitrocellulose, and probed with nick-translated chlamydial DNA. By this method, C. trachomatis serovar L2 EBs had three unique protein bands of 58,000, 25,700, and 17,000 molecular weight not seen in the reticulate bodies. The 17,000-molecular-weight protein and the 25,700-molecular-weight protein were identified in an acid-soluble protein fraction and were resistant to high-salt elution, similar to other procaryotic nucleoproteins. The 17,000-molecular-weight protein was also detected in preparations with isolated chromosomes from EBs. Preliminary characterization indicated that the protein-DNA interaction was principally charge related.